Efficacy of pembrolizumab in patients with advanced cancer of unknown primary (CUP): a phase 2 non-randomized clinical trial. Issue 5 (20th May 2022) - Raghav, Kanwal P; Stephen, Bettzy; Karp, Daniel D; Piha-Paul, Sarina A; Hong, David S; Jain, Dipti; Chudy Onwugaje, Dilichukwu O; Abonofal, Abdulrahman; Willett, Anneleis F; Overman, Michael; Smaglo, Brandon; Huey, Ryan W; et al.
Abstract : Background: Cancer of unknown primary (CUP) is an aggressive rare malignancy with limited treatment options. Data regarding clinical activity of immune checkpoint inhibitors in CUP is lacking. Therefore, we evaluated the efficacy of pembrolizumab, a programmed cell death-1 inhibitor, in patients with CUP. Methods: The study was designed as a phase 2 basket trial for independent rare tumor cohorts including CUP. Adult patients with CUP who had progressed on previous systemic therapy, performance status 0/1 and measurable disease per Response Evaluation Criteria in Solid Tumors (RECIST V.1.1) were eligible. Patients received pembrolizumab (200 mg) intravenously every 21 days. Twenty-nine patients were enrolled and treated between August 2016 and June 2020. The primary endpoint was non-progression rate (NPR) at 27 weeks (NPR-27) per immune-related RECIST. Key prespecified secondary endpoints were confirmed objective response rate (ORR), safety, duration of response (DoR), progression-free survival (PFS) and overall survival (OS). Pretreatment biopsies were examined for biomarkers of response (programmed cell death ligand-1 (PD-L1) expression and tumor infiltrating lymphocytes (TILs)). Results: Among 25 (of 29 enrolled) eligible and evaluable patients, 14 (56%) had poorly differentiated carcinoma. Patients received a median of two lines of therapy prior to enrollment. Median follow-up was 27.3 months. NPR-27 was observed in seven patients (28.0% (95% CI: 12.1 to 49.4)). ORR was 20.0% (95% CI: 6.8 to 40.7) with five patients achieving immune-related partial response with median DoR of 14.7 months (95% CI: 9.8 to 19.6). Median PFS and OS were 4.1 (95% CI: 3.1 to 5.1) and 11.3 (95% CI: 5.5 to 17.1) months, respectively. Treatment-related adverse events of any and grade ≥3 were seen in 19 (76%) and 4 (16%) patients, respectively. One (4%) patient had grade 3 immune-related acute kidney injury requiring treatment discontinuation. Neither PD-L1 nor TILs were associated with NPR-27. Both positive PD-L1 staining (44.4% vs 6.3%; p=0.040) and intense TIL infiltration (44.4% vs 6.3%; p=0.040) were associated with response. Conclusion: Pembrolizumab showed encouraging efficacy in patients with CUP with acceptable safety profile. Trial registration number: NCT02721732 .